Bangime: secret language, language isolate, or language island? A computer‐assisted case study - Hantgan, Abbie; List, Johann‐Mattis (Papers in Historical Phonology, 2022)
We report the results of a qualitative and quantitative lexical comparison between Bangime and neighboring languages. Our results indicate that the status of the language as an isolate remains viable, and that Bangime speakers have had different levels of language contact with other Malian populations at various points throughout their history. Bangime speakers, the Bangande, claim Dogon ancestry. The Bangande portray this connection to Dogon through the fact that the language has both recent borrowings from neighboring Dogon varieties and more rooted vocabulary from Dogon languages spoken to the east from whence the Bangande claim to have come. Evidence of multilayered long‐term contact is clear: lexical items have even permeated even core vocabulary. However, strikingly, the Bangande are seemingly unaware that their language is not intelligible with any Dogon variety. We hope that our fiindings will influence future studies on the reconstruction of the Dogon languages and other neighboring language varieties to shed light on the mysterious history of Bangime and its speakers.